The relationship of motor response-ability to the level of skill performance for the female futsal players of Al-Zawraa Sports club - ALATTAR, Samer; al-Maliki , Mohammed (Journal of Physical Education, 2024)
The current study dealt with identifying the type of relationship between two variables, which are the motor response ability and the skill performance of the players of the Al-Zawraa Futsal Club, which is participating in the Iraqi Premier Futsal League for Women in the (2022-2023) season. The researchers used the descriptive approach in a comparative manner to suit the nature of the research, as they conducted a test of the two variables. After ensuring the validity and suitability of the tests for the research sample by extracting the scientific foundations for the tests that were applied to(70 female athletes), while the main experimental trial for the research sample included(16) female players who performed the motor response ability test with the skill performance test, and after extracting and processing the results, it was found that there A positive and reciprocal relationship between the two variables, as skill performance is affected by the level of combinatorial abilities.